The Societal Consequences of Insecure Employment: Job Insecurity, Stress, and Employee Retention In A Developing Country Context - Eny Nuryani Resmiati; Edwar Agustian (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2025)
Employee turnover has emerged as a critical concern in Indonesia's industrial sector, especially within manufacturing firms employing non-permanent labor contracts. The increasing prevalence of job insecurity and elevated work-related stress has prompted serious concerns regarding employee retention and organizational performance. This study aims to examine the influence of job insecurity and job stress on turnover intention in the context of a manufacturing company in West Java, Indonesia. The urgency of the research lies in addressing psychological and organizational challenges that directly impact workforce stability. A quantitative approach with a descriptive-verificative design was employed. Data were collected from 145 employees using structured questionnaires and analyzed using path analysis to estimate direct and indirect effects. The study measured job insecurity, job stress, and turnover intention using validated instruments and tested their reliability and validity prior to analysis. The findings indicate that job insecurity has the most substantial effect on turnover intention, followed by job stress. Together, these variables explain 64.4% of the variance in turnover intention. The study reveals that perceived employment instability and psychological strain are key drivers of turnover behavior. Practical implications include the need for organizations to improve employment stability and implement stress management programs. This research contributes to human resource management literature by emphasizing the societal consequences of insecure employment in developing economies and recommends future studies to expand the model with broader psychological and organizational factors.